2021
DOI: 10.21203/rs.3.rs-558554/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Failed implementation of mobile access to electronic health records in homecare: a qualitative study

Abstract: BACKGROUNDDigitalization could optimize healthcare; however, many eHealth projects are unsuccessful. By analyzing reasons for unsuccessful eHealth implementation, we could gain important knowledge on how to achieve successful digitalization in primary care and homecare.The aim of this study is to describe the implementation process of a tablet computer with an mHealth app that provides mobile access to the electronic health record (EHR) in homecare in order to understand reasons for unsuccessful implementation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Despite the ubiquity of mHealth apps for health care consumers and providers, health information technology implementation is frequently unsuccessful [ 9 ]. Previous research has found that apps may not align with end-user behavior and organizational needs, essentially showing a mismatch between how the app is designed to function and how the intended end user expects it to work [ 10 - 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the ubiquity of mHealth apps for health care consumers and providers, health information technology implementation is frequently unsuccessful [ 9 ]. Previous research has found that apps may not align with end-user behavior and organizational needs, essentially showing a mismatch between how the app is designed to function and how the intended end user expects it to work [ 10 - 12 ].…”
Section: Introductionmentioning
confidence: 99%